MORFOLOGI VLADIMIR PROPP PADA DONGENG PEAU D'ANE DALAM KUMPULAN DONGENG LES PLUS BEAUX CONTES KARYA CHARLES PERRAULT - Dian Agustina Pratama (Jurnal SORA, 2019)
"Peau d'Ane" is one of the tales of Charles Perrault, a French writer. "Peau d'Ane" is included in a collection of "Les Plus Beaux Contes", which contains the works of Charles Perrault. "Peau d'Ane" is one of story about a princess but somehow the function of a prince as a hero doesn't appear in this fairy tale. This study uses the theory of fairy tales function according to Propp which divides functions in fairy tales into 31 and 7 action circles. The purpose of this study is to describe the functions and the circle of action in the "Peau d'Ane" fairy tale. This research using qualitative descriptive method. The results of the analysis. of functions in the "Peau d'Ane" show that there are 19 functions appear and 5 spheres of actions. These 19 functions form the storyline in the "Peau d'Ane" fairy tale, while in the 5 spheres of action appear as actors who have roles in the fairy tale.